The case for data sharing in traditional, complementary, and integrative medicine research - Jeremy Y. Ng (Integrative Medicine Research, 2025)
Traditional, complementary, and integrative medicine (TCIM) research encompasses a diverse range of health practices rooted in various cultural, philosophical, and historical frameworks. As global interest in conducting research in this field grows, the need for rigorous research to support the integration of evidence-based TCIM therapies into mainstream healthcare has become essential. Data sharing is critical to advancing TCIM research by enhancing reproducibility, fostering interdisciplinary collaboration, promoting ethical practices, and addressing global health challenges. Despite its benefits, numerous challenges are associated with data sharing in TCIM, including a lack of standardized practices, cultural sensitivity, intellectual property concerns, and technical barriers in resource-limited settings. This editorial explores the unique nature of TCIM research, emphasizing the importance of data sharing while acknowledging the complexities it entails. Implementing the CARE Principles for Indigenous Data Governance, which prioritize collective benefit, authority to control, responsibility, and ethics, offers a framework for ensuring that data sharing respects indigenous knowledge and cultural sensitivities. Strategies for overcoming barriers to data sharing include developing standardized protocols, investing in research infrastructure, and fostering a culture of openness and collaboration within the TCIM community and beyond. By advancing data sharing practices, TCIM research can contribute to evidence-based healthcare solutions and address global health disparities, ultimately improving health outcomes worldwide.